2016
DOI: 10.1039/c6ra15351h
|View full text |Cite
|
Sign up to set email alerts
|

A TiO2/PEO composite incorporated with in situ synthesized hyper-branched poly(amine-ester) and its application as a polymer electrolyte

Abstract: By in situ synthesizing hyper-branched poly(amine-ester) in TiO2/PEO nanocomposite, efficient ion transporting among the nano inclusions can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The results of this study confirmed that the increase in dopant molarity gives an effect on the increment of conductivity [11]. G. M. Hou, and co-worker, in 2016, showed a new polymer nanocomposite of nano-titanium dioxide/polyethylene oxide within situ synthesis hyper-branch poly (amine-ester) and its applications as a polymer electrolyte [12]. Al-Mokaram and his groups prepared Ppy/CH/TiO2 Nanocomposite Films [13].…”
Section: Introductionsupporting
confidence: 72%
“…The results of this study confirmed that the increase in dopant molarity gives an effect on the increment of conductivity [11]. G. M. Hou, and co-worker, in 2016, showed a new polymer nanocomposite of nano-titanium dioxide/polyethylene oxide within situ synthesis hyper-branch poly (amine-ester) and its applications as a polymer electrolyte [12]. Al-Mokaram and his groups prepared Ppy/CH/TiO2 Nanocomposite Films [13].…”
Section: Introductionsupporting
confidence: 72%
“…This change had also been reported in similar studies. Hou et al [ 29 ] studied the crystallinity of hyper-branched poly(amine-ester) (HBPAE)/HBPAE-g-TiO 2 /PEO electrolyte by in situ synthesis of hyperbranched poly(urethane)-doped TiO 2 /PEO composite materials. The lowest crystallinity of the SPEs was acquired when the TiO 2 content reached 15 wt.%, while the value showed a slight improvement as the TiO 2 content further increased.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the improvement in electrochemical and mechanical performance is greatly restricted. A method called in situ synthesis was recently proposed to introduce ceramic particles through reactions occurring among different elements or compounds [ 5 , 19 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The in situ synthesized ceramic particles possess clean surface and good dispersibility, excellent compatibility with the polymers, and high interface binding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, with increasing ceramic content, the ionic conductivity increases. The ionic conductivity reaches the maximum at the percolation threshold, such as 10 wt% LLZTO [ 75 ], 25 wt% LATP [ 92 ], 20 wt% LAGP [ 93 ], 5 wt% MnO 2 [ 90 ] and 7.5 wt% TiO 2 [ 94 ]. However, further increasing the ceramic content will block ion transmission and cause a decrease in ionic conductivity.…”
Section: + Conduction Mechanismmentioning
confidence: 99%
“…There are some criteria for the coating layer. First, the coating layer should have a similar surface energy to PEO for increasing the surface affinity between ceramic and polymer, greatly providing good compatibility and promoting Li + transportation at ceramic/polymer interfaces [ 94 , 170 ]. For example, PDA-coated LLZTO showed a lower contact angle of 76°, whereas pristine LLZTO showed a higher contact angle of 116° with PEO solution (Fig.…”
Section: Interfacial Engineeringmentioning
confidence: 99%